LES/TPDF investigation of the effects of ambient methanol concentration on pilot fuel ignition characteristics and reaction front structures. (1st March 2021) - Xu, Shijie; Pang, Kar Mun; Li, Yaopeng; Hadadpour, Ahmad; Yu, Senbin; Zhong, Shenghui; Jangi, Mehdi; Bai, Xue-song
Highlights: LES with state-of-the-art approach (TPDF) is used to study a dual-fuel spray flame. A negative correlation between Fm and the value of the first stage HRR is observed. It is found that ambient methanol affects the n-heptane LTC and cool flame structure. Abstract: Large-eddy simulations with a transported probability density function model coupled with a finite-rate chemistry is applied to study the ignition process of an n-heptane spray in a constant volume chamber with a premixed methanol-air atmosphere under conditions relevant to reactivity controlled compression ignition (RCCI) engines. Three reacting spray cases with initial methanol-air equivalence ratio ( ϕ m ) ranging from 0 to 0.3 are investigated at an initial temperature of 900 K. The case setup is based on the Engine Combustion Network Spray-H configuration, where n-heptane fuel is used. The effects of the ambient methanol-air equivalence ratio on the ignition characteristics and the reaction front structures in n-heptane/methanol RCCI combustion are studied in detail. It is found that the ambient methanol affects the low temperature chemistry of n-heptane, which results in a change of spatial distribution of key species such as heptyl-peroxide, and therefore the cool flame structure. With the presence of methanol in the ambient mixture cool flame is found in the entire fuel-rich region of the n-heptane jet, while when methanol is absent in the ambient mixture, the cool flame is established only around the stoichiometric mixture close to the n-heptane injector nozzle. In general, both low- and high-temperature ignition stages of n-heptane ignition are retarded by the methanol chemistry. An increase in ϕ m leads to a decrease of the peak heat release rate of the n-heptane first-stage ignition. The chemistry of methanol inhibits the n-heptane ignition by decreasing the overall hydroxyl radicals (OH) formation rate and reducing the OH concentration during the transition period from the first-stage ignition to the second-stage ignition. As a result, the transition time between the two ignition stages is prolonged. Under the present lean methanol/air ambient mixture conditions, the impact of methanol on n-heptane ignition has a tendency of reducing the high-temperature, fuel-rich region, which is in favor of soot reduction.